Elevated C5a Plasma Concentrations in Mongolian Patients with Atherosclerotic Vascular Diseases - Shagdarsuren, Gansuvd; Dashbaljin, Jargal; Togtokh, Ariunaa; Sonomjamts, Munkhbayarlakh; Shagdarsuren, Erdenechimeg (Central Asian Journal of Medical Sciences, 2018)
Objectives: Complement activation product C5a is increased in acute cardiovascular events and infl ammation. However, investigation of C5a in patients with atherosclerotic vascular changes among Mongolian populations is still lacking. Methods: A total of 43 patients were selected using special criteria for this study. Plasma C5a and lipid levels were measured by high-sensitive enzyme-linked immune sorbent assay and colorimetric enzyme assay at the Mongolian National University of Medical Sciences, Core Laboratory and Second General Hospital. All data were analyzed for normality and then parametric or nonparametric tests using GraphPad Prism 6.0 software. The Pearson r correlation analysis was performed using Microsoft Excel. Results: Patients were divided into a healthy group ((n=23, carotid intima-media thickness (cIMT) <0.7 mm)) and a group with atherosclerosis (n=20 with cIMT >1.0 mm by Doppler-ultrasound imaging). The suffi cient number of patients within groups was approved by using column statistical analysis. A signifi cantly elevated plasma C5a protein concentration was found in patients with atherosclerosis compared to healthy controls (276.28±24.82 vs. 61.56±4.35 pg/mL, P<0.0001), which was directly correlated with increased total plasma cholesterol levels (r=0.68, P<0.01). Conclusion: Our study supported the notion that complement anaphylatoxin C5a may be involved in the pathogenesis of atherosclerotic vascular diseases.